A new approach to managing work-related road traffic injury: The development of a health investment framework - Warmerdam, A.; Newnam, S.; Sheppard, D.; Griffin, Mark; Stevenson, M. (Taylor & Francis, 2017)
© 2017 Taylor & Francis Group, LLC. Objective: Statistics indicate that employees commuting or traveling as part of their work are overrepresented in workplace injury and death. Despite this, many organizations are unaware of the factors within their organizations that are likely to influence potential reductions in work-related road traffic injury. Methods: This article presents a multilevel conceptual framework that identifies health investment as the central feature in reducing work-related road traffic injury. Within this framework, we explore factors operating at the individual driver, workgroup supervisor, and organizational senior management levels that create a mutually reinforcing system of safety. Results: The health investment framework identifies key factors at the senior manager, supervisor, and driver levels to cultivating a safe working environment. These factors are high-performance workplace systems, leader–member exchange and autonomy, trust and empowerment, respectively. The framework demonstrates the important interactions between these factors and how they create a self-sustaining organizational safety system. Conclusions: The framework aims to provide insight into the future development of interventions that are strategically aligned with the organization and target elements that facilitate and enhance driver safety and ultimately reduce work-related road traffic injury and death.